Lightning strike fatalities: three case reports of military personnel in Malaysia - Ahmad, Rozali; Hussain, Khairuddin; Mohd Sidik, Sherina; Chia, L. M.; K., Yaakop (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2012)
Lightning strikes have been known to cause fatal injuries. However, these cases have not been adequately highlighted in Malaysia. This paper reports on three cases of military personnel who lost their lives after being struck by lightning while on operational duties. It is extremely important to implement adequate safety measures and ensure that all military personnel are adequately trained on emergency procedures, such as Cardio Pulmonary Resuscitation (CPR) to prevent casualties of lightning strikes in future. This paper addresses several issues to avoid similar occurrences; the importance of taking extra safety precautions and recognizing signs of lightning strikes, as well as the immediate administration of CPR on victims.